The National Geography Curriculum for Basic Education in Portugal: Theory and Practices by Geography Teachers - Martins, Maria Felisbela Sousa (2012)
Centered on issues related to the National Geography Curriculum for Basic Education in Portugal this paper explores the (re)interpretations by Geography teachers trained at the Faculty of Arts of the University of Porto in the implementation of the National Curriculum, that is, in their teaching practices.